Analysis of House Conditions and Optimization of Aid Funds Based on Criteria for Unlivable Houses in Lubuklinggau Timur II District, Lubuklinggau City - Yusmarizal, Yusmarizal; Hidayat, Benny; Yossyafra, Yossyafra (Universitas Negeri Padang, 2024)
This research addresses the problem of public knowledge of uninhabitable houses and the difficulty in identifying houses that do not meet community housing standards, to provide criteria for uninhabitable houses as well as optimize the rehabilitation assistance budget carried out by the Government. This research uses a quantitative descriptive method by collecting data through questionnaires, field observations, and documentation on 69 sample houses. The results of the analysis categorize the level of damage to the house into three categories, namely heavy, moderate, and light damage. From the research results of 69 sample houses, it was found that only 59 houses met the requirements for the uninhabitable house rehabilitation assistance program. In optimizing the allocation of aid funds, the level of damage to the house must be taken into account. With a more objective approach, rehabilitation housing programs can be more effective and provide greater benefits to people in need.